Posttranslational Modifications of Intact Proteins Detected by NMR Spectroscopy: Application to Glycosylation1. (29th April 2015) - Schubert, Mario; Walczak, Michal J.; Aebi, Markus; Wider, Gerhard
Abstract Posttranslational modifications (PTMs) are an integral part of the majority of proteins. The characterization of structure and function of PTMs can be very challenging especially for glycans. Existing methods to analyze PTMs require complicated sample preparations and suffer from missing certain modifications, the inability to identify linkage types and thus chemical structure. We present a direct, robust, and simple NMR spectroscopy method for the detection and identification of PTMs in proteins. No isotope labeling is required, nor does the molecular weight of the studied protein limit the application. The method can directly detect modifications on intact proteins without sophisticated sample preparation. This approach is well suited for diagnostics of proteins derived from native organisms and for the quality control of biotechnologically produced therapeutic proteins.